2015
DOI: 10.1523/jneurosci.2458-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccade Control Signals in the Cerebellum

Abstract: Microsaccades, the small saccades made when we try to keep the eyes still, were once believed to be inconsequential for vision, but recent studies suggest that they can precisely relocate gaze to tiny visual targets. Because the cerebellum is necessary for motor precision, we investigated whether microsaccades may exploit this neural machinery in monkeys. Almost all vermal Purkinje cells, which provide the eye-related output of the cerebellar cortex, were found to increase or decrease their simple spike firing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…On the other hand, neurons in the posterior vermis, caudal fastigial nucleus, and interpositus nucleus of the cerebellum are related to the precise and adaptive control of saccades (Robinson and Fuchs, 2001; Dash and Thier, 2014). Recent studies reported that single neurons in the oculomotor vermis and caudal fastigial nucleus discharged both for macro- and micro-saccades (Arnstein et al, 2015; Sun et al, 2016). We previously reported that neurons in the monkey PPTg showed saccade-related activity modulation, some modulations were only associated with reward-related saccades consistent with neurons reported in the basal ganglia (Kobayashi et al, 2002; Okada and Kobayashi, 2009), while others exhibited this modulation with every saccade, including small fixational saccades, consistent with neurons in the cerebellum (Okada and Kobayashi, 2014).…”
Section: Therapeutic Effect Of Pptg Stimulation In Parkinson’s Diseasementioning
confidence: 99%
“…On the other hand, neurons in the posterior vermis, caudal fastigial nucleus, and interpositus nucleus of the cerebellum are related to the precise and adaptive control of saccades (Robinson and Fuchs, 2001; Dash and Thier, 2014). Recent studies reported that single neurons in the oculomotor vermis and caudal fastigial nucleus discharged both for macro- and micro-saccades (Arnstein et al, 2015; Sun et al, 2016). We previously reported that neurons in the monkey PPTg showed saccade-related activity modulation, some modulations were only associated with reward-related saccades consistent with neurons reported in the basal ganglia (Kobayashi et al, 2002; Okada and Kobayashi, 2009), while others exhibited this modulation with every saccade, including small fixational saccades, consistent with neurons in the cerebellum (Okada and Kobayashi, 2014).…”
Section: Therapeutic Effect Of Pptg Stimulation In Parkinson’s Diseasementioning
confidence: 99%
“…Surgeries were carried out under combination anesthesia with remifentanil and isoflurane under aseptic conditions (see Arnstein et al . () for details). Post‐operative analgesia was continued until full recovery.…”
Section: Methodsmentioning
confidence: 99%
“…The motivation to work on the fixation and saccade task was promoted by restricting fluid provisions outside the experiment (see Arnstein et al . () for details on the protocol).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations